Analisis Fatwa MUI Nomor 4 Tahun 2003 - Desriani Desriani; Zulfan Efendi Hasibuan; Risalan Basri Harahap (IAIN Padangsidimpuan, 2021)
Various kinds of culinary are rife in the middle of the city of padangsidimpuan by using thr name of processed food using a strange name. one of the branded products thet are currently becoming a tren in the community are meatballs with children, devil’s noodles, missile meatball cones and so on.Islam requires that the products to be consumed will be guaranteed to be halal and pure. Halal is not only from the type but also from the name. where in the explanation of the MUI Fatwa Number 4 of 2003 concerning standardization of halal fatwas, it is contained in the fourth section: the problem of using names and ingredients in point 1, namely “not to consume and use names and/or symbols of food/drinks that leat to kufr and falsehood”. From this background for naming processed foods in padangsidimpuan city based on MUI Fatwa Analysis Number 4 of 2003.This research is a field research. The research used is to collect data on the phenomena that occur. The data sources of this research are primary data and secondary data. Data collection techniques using field studies, namely ovservation, interviews and documentation.The results of this study indicate that traders or sesllers give the names of the foods they make with strange names because of the many business competitors. Based on the MUI Fatwa Number 4 of 2003, the author’s analysis of the naming of processed foods that are contrary to the MUI Fatwa are devil noodles, dragon whiskers, and devil’s chili chicken, while the names of processed foods that are allowed or not contrary to the MUI Fatwa Number 4 of 2003 such as meadballs with planet chicken because these names do not lead to kufr/falsehood as described in the MUI Fatwa.